2021
DOI: 10.3390/cancers14010023
|View full text |Cite
|
Sign up to set email alerts
|

Low BACH2 Expression Predicts Adverse Outcome in Chronic Lymphocytic Leukaemia

Abstract: Chronic lymphocytic leukaemia (CLL) is a heterogeneous disease with a highly variable clinical outcome. There are well-established CLL prognostic biomarkers that have transformed treatment and improved the understanding of CLL biology. Here, we have studied the clinical significance of two crucial B cell regulators, BACH2 (BTB and CNC homology 1, basic leucine zipper transcription factor 2) and BCL6 (B-cell CLL/lymphoma 6), in a cohort of 102 CLL patients and determined the protein interaction networks that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…6a ). A recent study showed that decreased BACH2 expression in CLL is associated with adverse outcomes 37 . Notably, the mutations we detected in this promoter were mostly clonal (median CCF = 0.99).…”
Section: Resultsmentioning
confidence: 99%
“…6a ). A recent study showed that decreased BACH2 expression in CLL is associated with adverse outcomes 37 . Notably, the mutations we detected in this promoter were mostly clonal (median CCF = 0.99).…”
Section: Resultsmentioning
confidence: 99%
“…It was revealed in our study that LEF1 might be downregulated and functionally associated with MLKL in sepsis. BACH2 is a key factor in B cell regulation, and low expression of BACHA2 can predict poor outcomes in chronic lymphocytic leukemia [7] It has been demonstrated that increased expression of BCL-2 contributes to tumor expansion, and impairment of BCL-2, considered an oncogene, has been implicated in the development of a wide range of cancerous manifestations, including lymphomas [11]. In the eld of sepsis, BCL2 is closely associated with multiple diseases caused by sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…We identified BLCA-dependent genes based on the CERES score from the Depmap database. Essential genes were defined as genes with CERES scores <-1 in more than 75% of BLCA cell lines [25].…”
Section: Identification Of Essential Genes For the Development Of Blcamentioning
confidence: 99%